Drying Process Study of Hydrothermal Carbonized Biomass - Reyes-Salinas, A; Cubillos-Montecino, F; Diaz-Robles, L; Vallejo-Gallardo, F (Taylor and Francis Ltd., 2022)
Residual biomass is a low-cost raw material, although it must overcome some limitations such as its low calorific value, seasonal availability, and high humidity, which reduces its quality as a fuel. Hydrothermal Carbonization (HTC) is an operation that increases the energy density of raw biomass, obtaining a final solid (hydrochar) with higher calorific value and hydrophobic properties. This work studies the drying process of the hydrochar obtained from Pinus radiata sawdust in an indirect rotary dryer. The process was modeled by the Schlünder and Mollekopf penetration model. The fit obtained with the experimental data indicates an acceptable performance. The mass transfer coefficient varied between 69.4 and 131.7 W/m2·K (average solid temperature) and from 83.9 to 165.8 W/m2·K (100 °C as solid temperature). The mixing number (Nmix) determined was between 19.19 and 24.39, comparable to that reported in the literature. The significant effects on the process were heating steam pressure and the turning speed of the drum. Finally, through a response surface analysis, the optimum nondimensional drying rate value was determined: Vsec = 0.0040 kg H2O/kgdb ·s. © 2020 Taylor & Francis Group, LLC.